Role of protein kinases in stimulation of human polymorphonuclear leukocyte oxidative metabolism by various agonists. Differential effects of a novel protein kinase inhibitor. - Gerard, C (1986)
Isoquinoline sulfonamides have recently been shown to exert novel inhibitory effects on mammalian protein kinases by competitively binding to the ATP substrate site (Hidaka, H., M. Inagaki, S. Kawamoto, and Y. Sasaki, 1984, Biochemistry, 23: 5036-5041). We synthesized a unique analog of the previously reported compounds, 1-(5-isoquinolinesulfonyl) piperazine (C-I), in order to assess the role of protein kinases in modulating the agonist-stimulated oxidative burst of human polymorphonuclear leukocytes (PMN). Compound C-I, at micromolar concentration, markedly inhibited the release of superoxide anion from human PMN stimulated with phorbol myristate acetate or the synthetic diacylglycerol, 1-oleoyl-2-acetyl glycerol. These data are consonant with previously reported data which indicate that the calcium and phospholipid-dependent protein kinase, protein kinase C, serves as the intracellular receptor for these agonists. In contrast, superoxide anion production stimulated by the complement anaphylatoxin peptide C5a or the synthetic chemotaxin formyl-methionyl-leucyl-phenylalanine were not inhibited by C-I. These data suggest that parallel pathways exist for the agonist-stimulated respiratory burst of human neutrophils, only one of which utilizes the calcium and phospholipid-dependent protein kinase.